Hospital-based Analytical Study of Anti-thyroid Peroxidase Titre Among Type-2 Diabetic Patients Suffering from Thyroid Disorders - Jha, Rajneesh; Mishra, Amit; Mishra, Meena Kumari; Mallick, Ram Lala (Birat Journal of Health Sciences, 2019)
Introduction: Thyroid hormones control growth, development and metabolic processes. Either excessive or deficient secretion of these hormones interfere with metabolism. Thyroid hormones, therefore, can alter a person’s blood sugar. Relatively, thyroid peroxidise enzyme plays a key role in thyroid hormone production. The individuals who suffer from autoimmune thyroid diseases produce auto antibodies against thyroid peroxidise (called anti-TPO). Objectives: We aimed to investigate an association of anti-TPO titer among type-2 diabetic patients suffering from thyroid disorders attending the local hospital. Methodology: Based on findings of thyroid variables [such as total triiodothyronine (TT3 ), thyroxine (T4 ) and thyroid stimulated hormone (TSH)], type-2 diabetic patients were categorized into Euthyroidism, Subclinical hypothyroidism and Hypothyroidism. In this hospital-based prospective study, venipuncture was performed to collect anti-cubital venous blood samples (n=100) from January to December, 2018. After separation of sera, estimation of certain parameters such as TT3, T4 , TSH and anti-TPO were carried out for correlative analyses. In this aspect, based on WHO guidelines, the patients who had fasting as well as postprandial blood sugar levels > 126 and 200 mg/dl were confirmed for diabetes mellitus. In addition, if these patients exhibited HbA1C levels > 10.8 %, they were enrolled into the 1 study. The patients who were hyperglycemic (with fasting as well as post-prandial blood sugar levels < 126 and 200 mg/dl) were excluded. Results: In the three groups as stated above, we observed that more a rise in level of glucose, greater were the values of TSH and anti-TPO. Conclusion Such findings emphasize and put an impact in situations of thyroid abnormality among type-2 local diabetic population.